Clinical manifestation and treatment of small intestinal lymphangioma: A single center analysis of 15 cases - Wang, Zhen-zhen; Shen, Ling-yan; Zhou, Jing-jing; Tang, Jia-li; Ye, Li-ping; Shen, Chen-bo; Li, Shao-wei; Zhou, Xian-bin (Frontiers in Medicine, 2022)
Background: Small intestinal lymphangioma is a very rare benign lesion. Thus far, the literature on small intestinal lymphangioma has mainly involved case reports. The present study retrospectively examined the clinical features of patients with a pathological diagnosis of small intestinal lymphangioma. Methods: From January 2010 to January2021, 15 patients were pathologically diagnosed with small intestinal lymphangioma. The age, gender, clinical manifestation, computed tomography (CT) findings, endoscopic findings, localization of the lesion, treatment method, complications and follow-up were retrospectively analyzed. Results: Most of the patients had no symptoms, and those with symptoms had melena or abdominal pain. Lymphangioma was located in the duodenum in 9 cases (60.0%), jejunum in 2 (13.3%), jejunal-ileal junction with mesentery involvement in 1 (6.7%) and ileum in 3 (20.0%); 3 cases (20.0%) had multiple lesions, and the other 12 (80.0%) had single lesions. The median size of the lesions was 0.8 cm. Thirteen cases were found by endoscopy, and nine cases of them had white-colored spots on the surface. Ten cases (66.7%) underwent endoscopic treatment, 3 (20.0%) underwent surgical treatment, and 2 (13.3%) were followed up. Postoperative acute pancreatitis developed in one patient after endoscopic resection of duodenal papillary lymphangioma; postoperative abdominal bleeding occurred in one patient with jejunal lymphangioma who underwent partial small bowel resection. Conclusion: Small intestinal lymphangioma is extremely rare, and its clinical manifestations are nonspecific. Endoscopy is of great value in the diagnosis of small intestinal lymphangioma. Depending on the clinical manifestations, the size, location and scope of the lesions, follow-up, endoscopic treatment and surgery can be selected.